An overview of the most important medicinal plants effective on the strength of memory and mind in Iranian ethnobotany - Behrooz Farzan; Saber Abbaszadeh; Gholam Basati; Hassan Teimouri (GarVal Editorial Ltda., 2019)
Context: Physiologically, memory is created by changes in the synaptic conductivity from one neuron to the next neuron, leading to the emergence of new or facilitating pathways to guide messages in the neuronal circuits of the brain. Throughout the life in today's industrial conditions in which memory impairment is occurring at a faster pace, humans seek to figure out methods that prevent the development of related disorders and improve memory. The role of medicinal plants in learning and memory is one of the areas that have drawn substantial attention. Hence, this study introduces some of the most effective medicinal plants with memory improving properties according to Iranian ethnobotanical documents. Aim: To analyze some of the most effective medicinal plants with memory-enhancing properties according to the Iranian ethnobotanical documents. Methods: The data for this systematic review were collected from six popular databases including Institute for Scientific Information, PubMed, Google Scholar, Scientific Information Database, Magiran, and Scopus and included in the search terms the words "memory enhancement", "ethnobotany", "herbal drug", "Iran", "medicinal plants", "extracts", and "essential oils". The present dataset finally included 43 published articles. Results: Based on the available evidence of the studies on Iranian ethnobotany, certain medicinal plants such as Achillea wilhelmsii, Avena sativa, Boswellia papyrifera, Erucaria hispanica, Helianthus annuus, Ixiolirion tataricum, Lagochilus acutilobus, Pistacia atlantica, Pistacia khinjuk, Sinapis abyssinica, Spinacia oleracea, and Vicia sativa are among the plants that improve the mind. Conclusions: According to the findings found in this review, there is evidence that the plants that grow in Iranian territory have beneficial effects on the memory enhancement.